The Effect of Competence and Motivation on Employee Performance: A Short Review - Desi Susanti; Vyka Nur Amalia (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of writing this article is a narrative literature review of 3 (three) articles that discuss the influence of competence and motivation on employees, aiming to identify and summarize previously published articles without any criticism for the articles reviewed. The results of the review showed that to obtain tested explanatory findings on the effect of (1) competence and work motivation on employee performance, (2) competence on employee performance, (3) work motivation on employee performance, (4) competence on employee work motivation on PD. BPR Bank Buleleng 45. The research design in this study was causal quantitative. The use of analytical methods in this study is correlation analysis and regression analysis with T Count Test and F Test. The results showed that the tcount Hypothesis Test = 11.339 > t-table = 2.009 then Ha was accepted and Ho was rejected, meaning that there is a significant influence between Competence and Performance. Test Hypothesis t-count = 7.660 > t-table = 2.009 then Ha is accepted and Ho is rejected, meaning that there is a significant influence between Motivation and Performance. Test Hypothesis F count = 65.361 > F table = 3.19 then Ha is accepted and Ho is rejected, meaning that there is a significant influence between Competence and Motivation together on Employee Performance. The sampling technique uses saturated samples, so that all members of the population are sampled in this study. The data retrieval technique using questionnaires and data analysis used is multiple regression analysis. The results showed that there was a positive and significant influence between competency and motivation variables on employee performance.